Boot Camp Translation for the prevention of type 2 diabetes (T2D) in Fort Collins Hispanic/Latino adolescents - Annameier, Shelly, author; Schwartz, Laura, author; Haemer, Matthew, author; Shomaker, Lauren, author (Colorado State University. Libraries, 2017)
~50% of Hispanic/Latinos in the US will develop type 2 diabetes (T2D). Adolescent-onset T2D has an aggressive disease course, earlier mortality, and is a growing health concern. Standard lifestyle interventions have poor adherence and sustainability in adolescents at-risk for T2D. Psychosocial stressors and depressive symptoms may pose additional challenges for making lifestyle changes. There is a critical need for new approaches to preventing T2D in adolescents. Through a community-based participatory research program, "Boot Camp Translation," we examined evidence-based programs and cultivated culturally-tailored ideas for more effective prevention efforts, including launching focus groups to gather feedback for a comparative effectiveness trial.
022 - Shelly Annameier
Community based type 2 diabetes prevention in Hispanic/Latino adolescents
Keywords: type 2 diabetes; adolescence; Hispanic; community-based participatory research